2020
DOI: 10.1371/journal.pone.0229212
|View full text |Cite
|
Sign up to set email alerts
|

Training load and match-play demands in basketball based on competition level: A systematic review

Abstract: Basketball is a court-based team-sport that requires a broad array of demands (physiological, mechanical, technical, tactical) in training and competition which makes it important for practitioners to understand the stress imposed on the basketball player during practice and match-play. Therefore, the main aim of the present systematic review is to investigate the training and match-play demands of basketball in elite, sub-elite, and youth competition. A search of five electronic databases (PubMed, SportDiscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
155
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(166 citation statements)
references
References 50 publications
8
155
0
3
Order By: Relevance
“…Only 14.81% of the studies have analysed training and competition together. This is a problem, since examining the demands imposed on the players, from both training and competition, provide a context to create an optimal training environment [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only 14.81% of the studies have analysed training and competition together. This is a problem, since examining the demands imposed on the players, from both training and competition, provide a context to create an optimal training environment [16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the types of training situations have been evaluated in order to compare them with demands generated by competition and in an attempt to try to match them. However, it has only been found that the demands of training equal or exceed those in matches or conditioning exercises (11,12,13,16). Depending on the type of game situation used (small-sided games or full game), the load supported by the players is different.…”
Section: Training Demandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Team sports are characterized by high-intensity unilateral actions such as sprints, jumps or changes of direction (COD) [ 1 ]. On-court sports such as basketball and handball are two different team sports; however, given their characteristics and rules, many game actions, physiological demands and movement patterns are similar [ 2 , 3 ]. Speed actions, lateral movements, jumps or COD are skills common to both modalities and determinants of their athletic demands [ 2 ].…”
Section: Introductionmentioning
confidence: 99%